Energy efficiency of combined compressor-ejector vapor compression systems applied in industrial concentrators - Gjerasimovski, Aleksandar; Gjerasimovska, Natasha; Sarevski, Vasko (National Library of Serbia, 2025)
Investigations of the energy characteristics of thermocompression systems applied in industrial concentrators are presented in this paper. A significant increase of the energy efficiency in comparison with traditional industrial concentrators is achieved with the implementation of turbocompressor and/or ejector thermocom-pression. Single stage centrifugal compressors with water (R718) as a refrigerant are especially suitable for application in concentrators for production of fruit or grape concentrates because of the relatively small temperature difference between condensation and evaporation temperatures (Tc – Te). The heat pump cycle in the ejectors is realized with thermocompression of one part of the waste water vapor in the solution, which together with the primary steam from the boiler, or other heat generator, is used as a motive steam for the process of concentration. Several solutions of highly efficient single stage and multistage concentrator systems with turbocompressor and/or ejector thermocompression are proposed. The process of boiling - evaporation of the water from the treated solution in the concentrator is realized at low temperatures, under deep vacuum conditions, which is a guarantee for a high product quality. Due to the low costs of conventional fuels used in the processes of production of concentrate, the products made with these procedures are relatively low-priced, which makes them competitive on the market. A solution of a polygeneration system for production of electricity and thermal energy (steam and hot water) for the needs of technological processes in industrial concentration plants is presented.
Keywords: industrial concentrators; thermocompression; energy efficiency; polygeneration; fruit concentrate